Complete mitochondrial genome of Angiostrongylus malaysiensis lungworm and molecular phylogeny of Metastrongyloid nematodes - Yong, Hoi Sen; Song, Sze Looi; Eamsobhana, Praphathip; Lim, Phaik Eem (Elsevier, 2016)
Angiostrongylus malaysiensis is a nematode parasite of various rat species. When first documented in Malaysia, it was referred to as A. cantonensis. Unlike A. cantonensis, the complete mitochondrial genome of A. malaysiensis has not been documented. We report here its complete mitogenome, its differentiation from A. cantonensis, and the phylogenetic relationships with its congeners and other Metastrongyloid taxa. The whole mitogenome of A. malaysiensis had a total length of 13,516 bp, comprising 36 genes (12 PCGs, 2 rRNA and 22 tRNA genes) and a control region. It is longer than that of A. cantonensis (13,509 bp). Its control region had a long poly T-stretch of 12 bp which was not present in A. cantonensis. A. malaysiensis and A. cantonensis had identical start codon for the 12 PCGs, but four PCGs (atp6, cob, nad2, nad6) had different stop codon. The cloverleaf structure for the 22 tRNAs was similar in A. malaysiensis and A. cantonensis except the TΨC-arm was absent in trnV for A. malaysiensis but present in A. cantonensis. The Angiostrongylus genus was monophyletic, with A. malaysiensis and A. cantonensis forming a distinct lineage from that of A. costaricensis and A. vasorum. The genetic distance between A. malaysiensis and A. cantonensis was p = 11.9% based on 12 PCGs, p = 9.5% based on 2 rRNA genes, and p = 11.6% based on 14 mt-genes. The mitogenome will prove useful for studies on phylogenetics and systematics of Angiostrongylus lungworms and other Metastrongyloid nematodes.